Money laundering in Decentralized Finance : Business Implications and Regulatory Challenges in Europe - Mesias Bolanos, Emiliano; de Batz de Trenquelléon, Laure Sabine Marie; Zezula, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores the role of Blockchain Analytics in fighting money laundering within Decentralized Finance (DeFi) in the European Union. It shows how these tools help trace illicit transactions despite DeFi’s pseudonymity and decentralization. Case studies of Tornado Cash, Hydra Market, and ChipMixer demonstrate both the benefits and limitations of Blockchain Analytics in supporting AML enforcement in the EU.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses